Comportamiento agronómico del cultivo de PEPINO (Cucumis sativus L.) bajo diferentes tipos de sustrato orgánico - Rubira Morales, Edison Steven (2022)
The present investigation called "Agronomic behavior of the CUCUMBER (Cucumis sativus L.) crop was carried out in the La Bomba sector (Pichilingue) Mocache Canton, Los Ríos province- Ecuador; This study sought to answer the following study question: Will it be possible to have greater cucumber production using different types of organic substrates? For this reason, the following general objective was defined: to evaluate the agronomic behavior of the cucumber crop (Cucumis sativus L) under four types of organic substrates.